2018
DOI: 10.1080/21515581.2018.1504299
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising the coevolution of (dis)trust and control – a longitudinal case study of a public market

Abstract: Research into the dynamics of trust-control is still inconclusive. In this paper, we offer an in-depth understanding of how (dis)trust and control coevolve as embedded in multiple dimensions of context. The paper focuses on public markets, a context which is underrepresented in extant studies on trust and control. Our analysis is based on a longitudinal case study of interorganisational relationships (IOR) between boundary spanners representing purchaser and providers on a customer choice market for home care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Trust, as a distinctive element of relational contracting, included components such as interdependency and the exercise of discretion in making decisions about care packages. Trust within a contractual relationship is fundamental to successful practice between commissioners and providers (Hudson, 2004; Rubery et al ., 2013; Högberg et al ., 2018). For instance, research from the Netherlands reported that most of their municipalities have adopted a relational contractual approach to social care rather than a competitive tendering model, which was cited as a source of conflict in the past (Uenk and Telgen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Trust, as a distinctive element of relational contracting, included components such as interdependency and the exercise of discretion in making decisions about care packages. Trust within a contractual relationship is fundamental to successful practice between commissioners and providers (Hudson, 2004; Rubery et al ., 2013; Högberg et al ., 2018). For instance, research from the Netherlands reported that most of their municipalities have adopted a relational contractual approach to social care rather than a competitive tendering model, which was cited as a source of conflict in the past (Uenk and Telgen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With this focus, our study is particularly relevant to the nascent stages of PPPs, when partners have only little information about each other and mutual trust has yet to develop (Schilke and Cook 2013;Högberg et al 2018). In this state of increased uncertainty, simple heuristics are more salient than at later stages of the PPP, when assumptions about the partners are increasingly saturated with practical evidence from the partnership and trust interferes to a growing extent with institutional factors from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Korsgaard et al (2018) offer a compelling case for understanding trust dynamics and a practical guide to one of the methods. Högberg et al (2018) as well as Karhapää and Savolainen (2018) demonstrate the utility of longitudinal qualitative data analysis. The temporal dimensionwhether within-individual or between-organisationforms a specific level of analysis that can provide important insights that cannot be gleaned at another level.…”
Section: Multilevel Trust: Emerging Themes and Future Directionsmentioning
confidence: 95%
“…We begin the Special Issue with a paper by Korsgaard, Bliese, Kautz, Samson, and Kostyszyn (2018) focusing on trust dynamics over time. Next, continuing with the attention to time, two papers by Karhapää and Savolainen (2018) and by Högberg, Sköld, and Tillmar (2018) examine trust development in a merger and between public and private sectors. These are followed by Wang, Mather, and Seifert (2018) investigating job insecurity and trust in an economic downturn.…”
Section: The Papers In the Current Special Issuementioning
confidence: 99%
See 1 more Smart Citation